2021
DOI: 10.6061/clinics/2021/e2906
|View full text |Cite
|
Sign up to set email alerts
|

C-peptide level as predictor of type 2 diabetes remission and body composition changes in non-diabetic and diabetic patients after Roux-en-Y gastric bypass

Abstract: OBJECTIVES: Several predictors of type 2 diabetes mellitus (T2DM) remission after metabolic surgery have been proposed and used to develop predictive scores. These scores may not be reproducible in diverse geographic regions with different baseline characteristics. This study aimed to identify predictive factors associated with T2DM remission after Roux-en-Y gastric bypass (RYGB) in patients with severe obesity. We hypothesized that the body composition alterations induced by bariatric surgery cou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
4

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 33 publications
(37 reference statements)
0
3
0
4
Order By: Relevance
“…C-peptide is a biologically active short polypeptide (31 amino acids) that serves as a diagnostic biomarker to distinguish between type 1 and type 2 diabetes and is a strong indicator of insulin biosynthesis and insulin resistance syndrome (IRS) (21)(22)(23). Over the past decade, several studies demonstrated a biological effect of plasma circulating C-peptide on activating inflammatory signaling pathways (24,25).…”
Section: Association Of the C-peptide Levels With Circulatory Inflamm...mentioning
confidence: 99%
“…C-peptide is a biologically active short polypeptide (31 amino acids) that serves as a diagnostic biomarker to distinguish between type 1 and type 2 diabetes and is a strong indicator of insulin biosynthesis and insulin resistance syndrome (IRS) (21)(22)(23). Over the past decade, several studies demonstrated a biological effect of plasma circulating C-peptide on activating inflammatory signaling pathways (24,25).…”
Section: Association Of the C-peptide Levels With Circulatory Inflamm...mentioning
confidence: 99%
“…Portanto, diante da dificuldade de controle clínico da obesidade e DM2, apesar das novas terapias medicamentosas. considerando seu custo e limitação de qualidade de vida, o tratamento cirúrgico apresenta-se como opção de tratamento para indivíduos com obesidade grave (21) .…”
Section: Tratamento Nutricionalunclassified
“…O DM2 em pacientes submetidos a GDYR, apresenta possibilidade de aproximadamente 60% de remissão segundo as condições individuais de cada paciente (38) .O peptídeo C é uma substância formada por aminoácidos, produzido a partir da divisão da pró-insulina, portanto seus níveis são compatíveis com a mensuração da produção de insulina e indiretamente retrata a massa das células , portanto, seus níveis no pré-operatório considerados como preditor de remissão de DM2 após GDYR (21) .…”
Section: Schauer (2014) No Estudo the Surgical Treatment And Medicationsunclassified
See 1 more Smart Citation
“…Entretanto, o nível de peptídeo C igual e/ou maior a 3 reflete a reserva pancreática independentemente da idade, ou da duração do diabetes, sendo assim um preditor positivo para remissão da DM2. (22) De fato, os dois mecanismos principais parecem ser responsáveis pela melhora precoce do controle glicêmico após GDYR: (1) aumento da sensibilidade hepática à insulina induzida, em parte por restrição energética e (2) melhora da função das células β associada ao aumento da secreção de peptídeo 1 semelhante ao glucagon pós-prandial devido ao trânsito alterado de nutrientes. Observa-se uma melhora induzida pela perda de peso na sensibilidade periférica à insulina.…”
Section: Gasto Energéticounclassified